Prognostic value of health-related quality of life in elderly patients hospitalized with heart failure - Erceg, Predrag (Clin Interv Aging, 2019)
Purpose: Previous research has shown that poor health-related quality of life (HRQOL) is associated with adverse long-term prognosis in patients with heart failure (HF); however, there have been inconsistencies among studies and not all of them confirmed the prognostic value of HRQOL. In addition, few studies involved elderly patients and most focused on all-cause mortality and HF-related hospitalization as outcomes. The aim of our study was to determine whether HRQOL is a predictor and an independent predictor of long-term cardiac mortality, all-cause mortality, and HF-related rehospitalization in elderly patients hospitalized with HF. Patients and methods: This prospective observational study included 200 elderly patients hospitalized with HF in Serbia. HRQOL was measured using the Minnesota Living with Heart Failure questionnaire (MLHFQ). The median follow-up period was 28 months. The primary outcome was cardiac mortality, and all-cause mortality and HF-related rehospitalization were secondary outcomes. Survival analysis was conducted using the Kaplan–Meier method and Cox-proportional hazards regression. Results: Subjects with poor HRQOL (higher than the median MLHFQ score) had a higher probability of cardiac mortality (P=0.029) and HF-related rehospitalization (P=0.001) during long-term follow-up. Poor HRQOL was an independent predictor of cardiac mortality (HR: 2.051, 95% CI: 1.260–3.339, P=0.004), all-cause mortality (HR: 1.620, 95% CI: 1.076–2.438, P=0.021), and HF-related rehospitalization (HR: 2.040, 95% CI: 1.290–3.227, P=0.002). Conclusion: HRQOL is an independent predictor of long-term cardiac mortality in elderly patients hospitalized with HF. It also independently predicts all-cause mortality and HF-related rehospitalization. HRQOL could be used as a complementary clinical predictive tool in this patient population.